Are aqueous biphasic systems composed of deep eutectic solvents ternary or quaternary systems? - Passos, Helena (2017)
Deep eutectic solvents (DES) have emerged in the past few years as a new class of solvents with promising applications in several fields. In the present work, the application of DES (formed by binary mixtures of cholinium chloride and carboxylic acids or urea) as phase-forming components of aqueous biphasic systems (ABS) is investigated. The mechanisms associated with the phases demixing of ABS composed of DES, as well as the DES stability in aqueous solutions, are investigated to address the critical question whether DES-based ABS are in fact ternary or quaternary mixtures. It is shown that the DES integrity is destroyed in ABS by the disruption of the hydrogen-bonding interactions of the complex (a result of the isolated components preferential solvation by water), and as confirmed by a nonstoichiometric partition of the DES components between the coexisting phases. As a result, there are no “real” DES-based ABS; instead, there is the formation of ABS composed of four components, where the carboxylic acid used as the hydrogen-bond donor species seems to act as an additive. Finally, it is shown that these ABS have an outstanding potential to be used in extraction processes, as it is here demonstrated with the complete separation of two dyes. However, the volatile nature of short chain carboxylic acids and the nonstoichiometric partition of the DES components in ABS make the development of recovery and recycling steps more difficult to accomplish.